Panorama das pesquisas sobre o clima urbano no Brasil - Silva, Matheus Maciel da (2025)
Global climate change raises discussions on issues related to the direction of scientific research being developed. In this context, the present study aims to provide an overview of scientific production on urban climate in Brazil between 2010 and 2023 and contribute to the debate in this field, considering the context of global climate change that affects cities and Brazilian society. Through a literature review using bibliometrics, data processing techniques with the statistical software R, and statistical analysis of scientific articles published in Geography journals, as well as dissertations and theses from Brazilian universities, it was possible to outline a scenario of studies on urban climate in Brazil. A total of 466 scientific articles published in 50 Geography journals were analyzed, along with 175 graduate research works (129 dissertations and 46 theses) defended between 2011 and 2022 in Brazilian Geography postgraduate programs on urban climate. Using tables, graphs, and maps, it was observed that most of the research on urban climate is concentrated in the Southeast region. Additionally, it was found that the Southeast region hosts most of the universities conducting research on this topic, followed by the Northeast region. Among the scientific articles, the most analyzed cities were Recife (PE), Presidente Prudente (SP), and Belém (PA), while dissertations and theses mainly focused on the cities of São Paulo (SP), Dourados (MS), and Fortaleza (CE). A trend of increasing research on urban climate was noted across all types of studies. The most researched subsystem was the Thermodynamic one in all types of research. It is expected that this dissertation can serve as a basis for the formulation of public policies that encourage new research in this field.